Collaborative Action Research: Learning from a Failed Experience - Villalta Paucar, Marco Antonio (2019)
The aim of this article is to identify learning situations used in collaborative action research (CAR) in a rural school and a state university, based on the analysis of the strengths andchallenges of experience. From a methodological point of view, this is a case study of action research. The experience is analytically assessed by recognizing the strengths ―reciprocal recognition, appreciation of the other institutional body as a project partner with shared goals, and commitment of the inter-institutional educational actors to the students― and the challenges ―management of each institution’s internal contingencies for inter-institutional coordination, and institutional differences to distinguish intervention problems and goals. Based on the experience, the following learning situations are recognized: clarifying the goals of collaboration with reality criteria over the fair desire to achieve great transformations, and knowing the institutional administrative times and protocols that affect the inter-institutional collaboration.